PELAKSANAAN PEMILU DI INDONESIA BERDASARKAN PERSPEKTIF PANCASILA - Alvianus Kristian Sumual; Brilliant Johanes Maengko (INTELIGENSIA MEDIA, 2023)
Indonesia is a democracy where in its implementation it must adhere to the values that have been advocated in pancasila and the 1945 constitution as the basis of the state. The fourth precept of pancasila in the form of people's values has given birth to a principle called people's sovereignty where the people are the highest holders of sovereignty so that they have rights and obligations in every state administration. Elections are a form or implication of people's values and the enforcement of the principle of people's sovereignty in the democratic system in Indonesia. This study aims to determine the implementation of elections in terms of the Pancasila Specificity. The research method used in this study is a qualitative method where researchers use data sourced from various references such as books, journals, and various other references related to the topic under study. The results of the study concluded that the elections held in Indonesia are a form of democratic implementation based on the values of pancasila and the enforcement of the principle of people's unity as contained in pancasila as the basis of the state. However, the implementation of elections in the current era is far from the word pancasilais and has not accommodated the enforcement of the principle of people's sovereignty